Elevated ferroptosis is associated with elevated T cells in patients with heat stroke - Qi Cui; Zhongyan Xu; Daxin Lei; Chao Yu; Yuling Luo; Jie Zheng; Fukun Wang (Molecular Biology Reports, 2026)

Colletotrichum aotearoa B. Weir & P.R. Johnst causing leaf anthracnose in Lithocarpus litseifolius in China - Yuling Wang; Chang Liu; Guolin Cai; Ning Shu; Ziqiang Luo; Zixuan Qiu; Wuping Yan (Crop Protection, 2026)

A 3D porous KCuFC/collagen fibers/gelatin adsorbent for ultra-fast cesium capture from radioactive wastewater - Xiaoxia Ye; Shanyuan Chen; Juan Liu; Yuling Tang; Jianfei Zhou; Wei Luo; Jie Chen (Bioresource Technology, 2026)

Wheat properties shape microbial succession and flavor profile in high-temperature Daqu fermentation: a multi-omics perspective - Hongmei Wang; Yuling Shen; Sican Luo; Yongxin Hu; Fuli Wen; Qian Wang; Xi Shen; Hao Shi; Yiping Chen; Xiaozhong Zhong; Songtao Wang; Yang Wei; et al. (Food Research International, 2026)

Optimized cryoablation and combinatorial chemotherapy overcome sublethal survival in pancreatic cancer cells - Yukun Cao; Xin Li; Jing Shen; Shanshan Xie; Haoyang Lin; Yuling Luo; Xinli Zhou (International Journal of Refrigeration, 2026)

Responses of soil quality, enzyme-based ecosystem multifunctionality, and maize yield to short-term straw return with shallow-buried drip irrigation in Northeast China - Chutong Liu; Shucheng Liu; Boyang Hou; Yinong Zhao; Peilong Luo; Jing An; Yuling Zhang (Plant and Soil, 2026)

Ultrasound-assisted control of ice formation for DMSO-free cryopreservation of Jurkat cells - Xinli Zhou; Yuling Luo; Qiang Xu (International Journal of Refrigeration, 2026)

Early-rice straw return rnhances Cd accumulation in late-rice through increased soil Cd bioavailability and root uptake in a Cd-contaminated double-cropping rice system - Yuhui Zeng; Geyi Xu; Changsong Huang; Zhong Hu; Qian Qi; Yuling Liu; Xiao Deng; Yang Yang; Changjun Li; Si Luo (Journal of Environmental Sciences, 2026)

Corrigendum to ‘Exploring nonlinear responses of hydrodynamics and algal biomass to restoration measures in a eutrophic shallow urban lake’ [Journal of Contaminant Hydrology 281 (2026), 104986] - Pengfei Zhang; Huihuang Luo; Ke Zhang; Xiaoyu Cui; Yuling Huang; Shunxin Feng; Jiefan Niu (Journal of Contaminant Hydrology, 2026)

Exploring nonlinear responses of hydrodynamics and algal biomass to restoration measures in a eutrophic shallow urban lake - Pengfei Zhang; Huihuang Luo; Ke Zhang; Xiaoyu Cui; Yuling Huang; Shunxin Feng; Jiefan Niu (Journal of Contaminant Hydrology, 2026)

Prepare the umbrella before it rains: Transmission and rescue strategy of extreme climate shocks via susceptible-infectious-recovered-susceptible model - Qian Wang; Fang Nan; Yuling Luo (Ecological Economics, 2026)

Deciphering the mechanism of aristolochic acid I-driven hepatocellular carcinoma through integrated network toxicology and bioinformatics - Yuling Liang; Xing Ning; Qiuxia Chen; Shuqiao Zhang; Huishan Luo; He Yu; Tangjiaqi Li; Baoguo Sun; Shijun Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Effects of stocking density on growth and glucose metabolism in rainbow trout (Oncorhynchus mykiss) - Zhao Li; Zhuohang Feng; Shuangyue Luo; Yaxin Wang; Yuling Xu; Kang Dong; Zhishuai Hou; Qinfeng Gao; Shuanglin Dong (Aquaculture, 2026)

Adsorptive Removal of Ibuprofen from Aqueous Solution by UiO-66: Performance Evaluation and Mechanistic Insights - Luo Xinzeng; Liu Yuling; Wang Zhuoran; Rong Wang; Hao Shu; Hongli Wang (Water, Air, & Soil Pollution, 2026)

Recent heat wave across the Yunnan-Guizhou plateau and its impact on alpine lakes - Jiabin Peng; Junxu Chen; Xiaohui Pan; Yuling Luo; Siqi Feng; Tie Liu; Xi Chen (Journal of Cleaner Production, 2026)

Physicochemical properties, microbial diversity, metabolites and their potential relationships of traditional Chinese Zhacai fermented for different periods - Xinyi Wang; Yuanli Luo; Yuanqing Gu; Ting Ren; Yuling Liu; Xinhui Wang; Nan Zhao; Xin Nie; Dayu Liu; Zhiping Zhao (International Journal of Food Microbiology, 2026)

Hybrid evaporative-fan cooling vest: multi-scale cooling performance evaluation - XingLan Wang; Guang Yang; ShouXin Zhang; XiaoShan Yan; Yuling Luo; Suqin Chang; Xiaohui Zheng (Energy and Buildings, 2026)

Differences in nighttime radiance across urban residential communities in China - Yi Zhou; Yuling Jin; Gaohui Wen; Xianhui Hu; Hao Zhou; Yuchao Luo; Guohua Zhou; Haile Zhao (Journal of Environmental Management, 2025)

Zeolitic imidazolate frameworks exert bioenergetic modulation via the cAMP/PKA/CREB signaling pathway to accelerate periodontal regeneration - Weiqiang Hu; Xueshen Qian; Xuxin Lin; Qianqian Chen; Zekai Wu; Ziqin Chen; Zhenzhu Xue; Yuling Chen; Xiongcheng Xu; Kai Luo (Chemical Engineering Journal, 2025)

Recombinant PD1 liposome loading nintedanib for pulmonary fibrosis therapy in mice - Qian Luo; Ying Xie; Jiarui Xu; Yuxin Ren; Shuyuan Xiong; Hongrui Zhang; Yuling Chen; Haocheng Chen; Jinling Wang; Pengyu Huang; Liyu Sun; Peishan Li; et al. (Chemical Engineering Journal, 2025)

Anthropogenic aerosol feedbacks intensify air pollution and weather variability over China - Jixiang Li; Haipeng Yu; Andrea Pozzer; Kai Tang; Chenhui Jia; Zeyong Hu; Siyu Chen; Yunsai Zhu; Yuling Hu; Bofei Zhang; Hongyu Luo; Zekui Jiang; et al. (Atmospheric Environment, 2025)

Microalgae-induced changes in the rhizosphere microbiome improve saline-alkali tolerance of Perilla frutescens - Yunmei Zhang; Shuiwen Luo; Xuyang Gu; Wenshan Gao; Chenxing He; Ziyi Wang; Menghang Cheng; Yuling Liang; Dandan Cao; Jianfeng Liu (Journal of Applied Phycology, 2025)

Assessment of stability differences among various grassland biomes under severe drought in the northern China and Tibetan Plateau - Haile Zhao; Yi Zhou; Xin Chen; Yuan Qi; Yuyang Chang; Yuchao Luo; Xingjie Yin; Yuling Jin; Zhihua Pan; Pingli An (Agriculture, Ecosystems & Environment, 2025)

Cuproptosis is involved in small intestinal toxicity in the paraffins during pregnancy - Juan Tang; Zemin Xu; Mengna Jiang; Chao Luo; Xiaoyan Li; Yuling Jiang; Yi Qu; Jialing Ruan; Xiaoke Wang; Meihua Zheng; Wing-Cheung Law; Xinyuan Zhao (Toxicology Letters, 2025)

Preparation of Co-Ce modified sludge-based catalyst and its application in CO2 photothermal catalytic reduction - Shu Hao; Luo Xinzeng; Liu Yuling; Jia Yang; Dou Chuanchuan; Li Bo (Fuel, 2025)

Investigation of the dynamics and influencing factors of deepwater condensate field leakage - Qiuyan Wang; Xuerui Zang; Xiaoming Luo; Ce Wang; Yuling Lü (Process Safety and Environmental Protection, 2025)

Enhanced modeling of deep-water condensate transport and dispersion in the South China Sea - Qiuyan Wang; Yuling Lü; Xiaoming Luo; Xuerui Zang; Binxi Yue (Process Safety and Environmental Protection, 2025)

Evolutionary trends and photothermal catalytic reduction performance of carbon dioxide by MOF-derived MnOx - Dou Chuanchuan; Liu Yuling; Shu Hao; Li Shuaishuai; Shi Qiyuan; Luo Xinzeng (Fuel, 2025)

Improvement of plan quality in whole-breast radiation following BCS using feasibility DVH by less-experienced planners - Yun Zhang; Yuling Huang; Mingming Luo; Xingxing Yuan; Xiaoping Wang; Changfei Gong (Physical and Engineering Sciences in Medicine, 2025)
Variability in plan quality of radiotherapy is commonly attributed to the planner’s skill rather than technological parameters. While experienced planners can set reasonable parameters before optimization, less experienced planners face challenges. This study aimed to assess the quality of volumetric-modulated arc therapy (VMAT) in patients with left-sided breast cancer following breast-conserving surgery. Twenty-eight patients requiring whole-breast irradiation were randomly selected for inclusion. Each patient underwent two VMAT treatment plans: one optimized by an experienced planner (VMAT-EXP group) and the other designed by a less experienced planner using feasibility dose-volume histogram (FDVH) parameters from PlanIQ (VMAT-FDVH group). Both plans aimed to deliver a prescription dose of 50 Gy in 25 fractions to the planning target volume (PTV). Dosimetry parameters for the PTV and organs at risk (OARs) were compared between the two groups. Both the VMAT-EXP and VMAT-FDVH groups met the clinical plan goals for PTV and OARs. VMAT-FDVH demonstrated a PTV coverage and homogeneity comparable to those of VMAT-EXP. Compared to VMAT-EXP plans, VMAT-FDVH plans resulted in a significant reduction in the mean ipsilateral lung dose, with an average decrease of 0.9 Gy (8.5 Gy vs. 7.6 Gy, P < 0.001). The V5Gy and V20Gy of the ipsilateral lung were also reduced by 3.2% and 1.8%, respectively. Minor differences were observed in the heart, contralateral lung, breast, and liver. Personalized objectives derived from the feasibility DVH tool facilitated the generation of acceptable VMAT plans. Less experienced planners achieved lower doses to the ipsilateral lung while maintaining adequate target coverage and homogeneity. These findings suggest the potential for the effective use of VMAT in in patients with left-sided breast cancer following breast-conserving surgery, especially when guided by feasibility DVH parameters.

A new insight into the straw decomposition associated with minerals: Promoting straw humification and Cd immobilization - Yuling Liu; Haowei Zeng; Siduo Ding; Zhong Hu; Baiqing Tie; Si Luo (Journal of Environmental Sciences, 2025)

Impact of white matter hyperintensity location on outcome in acute ischemic stroke patients: a lesion-symptom mapping study - Yuling Peng; Dan Luo; Peng Zeng; Bang Zeng; Yayun Xiang; Dan Wang; Ying Chai; Yongmei Li; Xiaoya Chen; Tianyou Luo (Brain Imaging and Behavior, 2025)

The identification of signature genes and their relationship with immune cell infiltration in age-related macular degeneration - Jinquan Chen; Long Zhao; Longbin Zhang; Yiling Luo; Yuling Jiang; Peng H (Molecular Biology Reports, 2024)

Early-relief effects of tetrahedral DNA nanostructures-assisted depression therapy via modulates hippocampal neurogenesis and neuroplasticity - Yikai Dou; Xiao Yang; Yue Du; Weitong Cui; Yuling Luo; Jinxue Wei; Liansheng Zhao; Xiaoxiao Cai; Xiaohong Ma; Yunfeng Lin (Chemical Engineering Journal, 2024)

Mapping the dynamics of intensive forage acreage during 2008–2022 in Google Earth Engine using time series Landsat images and a phenology-based algorithm - Haile Zhao; Yi Zhou; Guoliang Zhang; Xin Chen; Yuyang Chang; Yuchao Luo; Yuling Jin; Zhihua Pan; Pingli An (Computers and Electronics in Agriculture, 2024)

Flotation mechanism and performance of air/condensate bubbles for removing oil droplets in the presence of acetic acid - Ce Wang; Yuling Lü; Hongwei Qi; Xiaoming Luo; Limin He (Science of The Total Environment, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Enhanced cadmium absorption and tolerance of rice epiphytic microbes by iron oxide nanoparticles - Siduo Ding; Zhong Hu; Yuling Liu; Li Li; Yuhui Zeng; Doudou Jin; Anwei Chen; Jihai Shao; Pin Su; Si Luo (International Biodeterioration & Biodegradation, 2024)

Effect of substrate morphology on characteristics of layer-by-layer self-assembly nanofiltration membrane for micropollutants removal - Juan Luo; Bowen Zhou; Chenjun Dong; Rongrong He; Yuling Zhang; Tao He (Desalination, 2024)

The impacts of aridification on land surface phenological changes in the farming-pastoral ecotone of northern China based on the climatic zoning method - Guoliang Zhang; Yuling Jin; Yi Zhou; Xin Chen; Haile Zhao; Sicheng Mao; Yuchao Luo; Siyu Chen; Xiuyue Wu; Zhihua Pan; Pingli An; Peiyi Zhao (Theoretical and Applied Climatology, 2024)

Smartphone-based electrochemical sensor for cost-effective, rapid and on site detection of chlorogenic acid in herbs using biomass-derived hierarchically porous carbon synthesized by a soft-hard dual template method - Wanjun Jiang; Zhonghui Zhuo; Xiaohua Zhang; Hai Luo; Lu He; Yuling Yang; Yangping Wen; Zhong Huang; Peng Wang (Food Chemistry, 2024)

Expression, purification, and enzymatic characterization of an extracellular protease from Halococcus salifodinae - Tao Hong; Ruru Pan; Juntao Ke; Yuqing Luo; Yuling Hao; Liangzhong Chen; Demei Tu; Yongpei Dai; Tingting Chen; Shaoxing Chen (Brazilian Journal of Microbiology, 2023)

Straw removal or non-removal affects cadmium (Cd) accumulation in soil–rice (Oryza sativa L.) system at different ambient air Cd levels - Si Luo; Yuling Liu; Bihao Luo; Yihao Yang; Li Li; Xin Fu; Liang Peng; Qingru Zeng (Journal of Environmental Management, 2023)

Numerical simulation of proppant transportation and placement in several complex structure fractures of a shale reservoir using a CFD approach - Mingliang Luo; Guoxu Jia; Yuling Yang; Xiaodong Si; Yunzhi Ge; Yongping Zhan; Mingjing Lu (Gas Science and Engineering, 2023)

Land use/cover changes and subsequent water budget imbalance exacerbate soil aridification in the farming-pastoral ecotone of northern China - Guoliang Zhang; Xin Chen; Yi Zhou; Haile Zhao; Yuling Jin; Yuchao Luo; Siyu Chen; Xiuyue Wu; Zhihua Pan; Pingli An (Journal of Hydrology, 2023)

Variation of Cd and As accumulation in crops under oilseed rape–rice rotation system in response to different contaminated rice straw-return methods - Yuling Liu; Haowei Zeng; Hanglv Zhou; Shijing Zhang; Baiqing Tie; Liang Peng; Qingru Zeng; Hua Peng; Si Luo (Plant and Soil, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Inhibition mechanisms of urea combined with nitrification on cadmium uptake by rice (Oryza sativa L.) seedlings - Li Li; Yuling Liu; Shijing Zhang; Siduo Ding; Xin Fu; Qingru Zeng; Liang Peng; Si Luo (Plant and Soil, 2023)

Assessing the influence of contaminated rice straw decomposition on the speciation of cadmium and arsenic in a naturally contaminated soil - Yuling Liu; Haowei Zeng; Hanglv Zhou; Shijing Zhang; Baiqing Tie; Qingru Zeng; Anwei Chen; Si Luo (Journal of Soils and Sediments, 2023)

Activation of cadmium under simulated solar illumination and its impact on the mobility of Cd in flooded soils - Bihao Luo; Chenfeng Xiao; Yuling Liu; Li Li; Liang Peng; Qingru Zeng; Si Luo (Environmental Science and Pollution Research, 2022)

Identifying impact of international trade and renewable energy consumption on environmental quality improvement and their role in global warming - Arshad Ahmad Khan; Sufyan Ullah Khan; Muhammad Abu Sufyan Ali; Adnan Safi; Yuling Gao; Jianchao Luo (Environmental Science and Pollution Research, 2022)

E-waste polycyclic aromatic hydrocarbon (PAH) exposure leads to child gut-mucosal inflammation and adaptive immune response - Guangcan Chen; Xia Huo; Xiuli Luo; Zhiheng Cheng; Yuling Zhang; Xijin Xu (Environmental Science and Pollution Research, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Osteogenic and angiogenic characterization of mandible and femur osteoblasts - Xue Yang; Jun Jiang; Ling Zhou; Song Wang; Mengjiao He; Kai Luo; Yuling Chen; Xiongcheng Xu (Journal of Molecular Histology, 2019)

Effects of livestock grazing on grassland carbon storage and release override impacts associated with global climate change - Guiyao Zhou; Qin Luo; Yajie Chen; Miao He; Lingyan Zhou; Douglas Frank; Yanghui He; Yuling Fu; Baocheng Zhang; Xuhui Zhou (Global Change Biology, 2019)
Predicting future carbon (C) dynamics in grassland ecosystems requires knowledge of how grazing and global climate change (e.g., warming, elevated CO 2 , increased precipitation, drought, and N fertilization) interact to influence C storage and release. Here, we synthesized data from 223 grassland studies to quantify the individual and interactive effects of herbivores and climate change on ecosystem C pools and soil respiration (Rs). Our results showed that grazing overrode global climate change factors in regulating grassland C storage and release (i.e., Rs). Specifically, grazing significantly decreased aboveground plant C pool (APCP), belowground plant C pool (BPCP), soil C pool (SCP), and Rs by 19.1%, 6.4%, 3.1%, and 4.6%, respectively, while overall effects of all global climate change factors increased APCP, BPCP, and Rs by 6.5%, 15.3%, and 3.4% but had no significant effect on SCP. However, the combined effects of grazing with global climate change factors also significantly decreased APCP, SCP, and Rs by 4.0%, 4.7%, and 2.7%, respectively but had no effect on BPCP. Most of the interactions between grazing and global climate change factors on APCP, BPCP, SCP, and Rs were additive instead of synergistic or antagonistic. Our findings highlight the dominant effects of grazing on C storage and Rs when compared with the suite of global climate change factors. Therefore, incorporating the dominant effect of herbivore grazing into Earth System Models is necessary to accurately predict climate–grassland feedbacks in the Anthropocene.

Synthesis, Characterization and Luminescent Properties of Anthracen- or Pyrene-Based Coumarin Derivatives - Hui Zhang; Li Zhao; Qinglong Luo; Yuling Zhao; Tianzhi Yu (Journal of Fluorescence, 2018)

Generation and Screening of T-DNA Insertion Mutants Mediated by Agrobacterium tumefaciens in the Garden Asparagus Stem Blight Pathogen Phomopsis asparagi - Yueping Zhang; Huaxiang Qu; Ping Zhao; Yongping Tang; Jingsong Zhou; Shaochun Luo; Yuling Yin; Guangyu Chen (Current Microbiology, 2017)

Construction and characterization of a bacterial artificial chromosome library for Camellia sinensis - Yuling Tai; Hao Wang; Chaoling Wei; Ling Su; Min Li; Liqun Wang; Zhaozhao Dai; Lingyun Shao; Jiayue Jiang; Meizhong Luo; Hua Yang; Weiwei Deng; et al. (Tree Genetics & Genomes, 2017)

Polybrominated diphenyl ethers, organochlorine pesticides, and polycyclic aromatic hydrocarbons in water from the Jiulong River Estuary, China: levels, distributions, influencing factors, and risk assessment - Yuling Wu; Xinhong Wang; Yongyu Li; Miaolei Ya; Hui Luo; Huasheng Hong (Environmental Science and Pollution Research, 2017)